2006
DOI: 10.2307/30032456
|View full text |Cite
|
Sign up to set email alerts
|

Being Victims or Beneficiaries? Perspectives on Female Genital Cutting and Reinfibulation in Sudan

Abstract: Female Genital Mutilation (FGM) or the more value neutral term, Female Genital Cutting (FGC) is widely practised in northern Sudan, where around 90% of women undergo the most extensive form of FGC, infibulation. One new approach to combating FGC in Sudan is to acknowledge the previously hidden form of FGC, reinfibulation (RI) after delivery, when the woman is sewn back so much as to mimic virginity. Based on a qualitative study in Khartoum State, this article explores Sudanese women's and men's perceptions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 25 publications
5
42
0
3
Order By: Relevance
“…Within the group of men from Somalia, infibulation was rejected by all the participants; "sunna," on the other hand (either Table II How FGM/C was seen by the 50 participants; more than an answer is possible FGM/C is considered a n Note: Out of 50 men, eight did not express any attitude clitoridectomy or cutting/scarification/pricking of the clitoris), was approved by half of the participants. Similar results were found by two qualitative studies conducted among men in Sudan (Berggren et al, 2006) and men and women in Somalia (Gele et al, 2013).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Within the group of men from Somalia, infibulation was rejected by all the participants; "sunna," on the other hand (either Table II How FGM/C was seen by the 50 participants; more than an answer is possible FGM/C is considered a n Note: Out of 50 men, eight did not express any attitude clitoridectomy or cutting/scarification/pricking of the clitoris), was approved by half of the participants. Similar results were found by two qualitative studies conducted among men in Sudan (Berggren et al, 2006) and men and women in Somalia (Gele et al, 2013).…”
Section: Resultssupporting
confidence: 86%
“…On the other hand, they often referred to the hadiths to justify the acceptance of the practice by Islam (Hadiths: stories handed down orally and later recorded, related to the actions and sayings of the Prophet Muhammad, which represent, after the Qur'an, the second source of Islamic teachings) (Scolart, 2004). The perception of the practice as an Islamic requirement has been reported among men in Sudan (Almroth et al, 2001;Herieka and Dhar, 2003;Berggren et al, 2006) and Gambia (Kaplan et al, 2013). Interviews with 222 male university students in Khartoum, Sudan, found that only 14 percent supported the practice.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations